Emergence of a Salmonella Rissen ST469 clinical isolate carrying blaNDM-13 in China - Huang, Yulan; Ma, Xiaobo; Zeng, Shihan; Fu, Liang; Xu, Heping; Li, Xiaoyan (Frontiers in Cellular and Infection Microbiology, 2022)
New Delhi metallo-β-lactamase-13 (NDM-13) is an NDM variant that was first identified in 2015 and has not been detected in Salmonella species prior to this study. Here we describe the first identification of a Salmonella Rissen strain SR33 carrying blaNDM-13. The aim of this study was to molecularly characterize SR33’s antimicrobial resistance and virulence features as well as investigate the genetic environment of blaNDM-13. The Salmonella Rissen SR33 strain was isolated from a patient with fever and diarrhea. SR33 belonged to ST469, and it was found to be multidrug-resistant (MDR) and to carry many virulence genes. Phylogenetic analysis showed that SR33 shared a close relationship with most of the Chinese S. Rissen ST469 strains. blaNDM-13 was located in a transmissible IncI1 plasmid pNDM13-SR33. Sequence analysis of blaNDM-13-positive genomes downloaded from GenBank revealed that a genetic context (ΔISAba125-blaNDM-13-bleMBL-trpF) and a hybrid promoter (consisting of −35 sequences provided by ISAba125 and −10 sequences) were conserved. ISAba125 was truncated by IS1294 in three plasmids carrying blaNDM-13, including pNDM13-SR33. To our knowledge, this is the first report of blaNDM-13 carried by Salmonella. The emergence of blaNDM-13 in a clinical MDR S. Rissen ST469 strain highlights the critical need for monitoring and controlling the dissemination of blaNDM-13. blaNDM-13 carried by a transmissible IncI1 plasmid may result in an increased risk of blaNDM-13 transmission. IS1294 may be involved in the movement of blaNDM-13.